Dharma Seorang Raja dalam Medan Perang Kurukṣhetra (Kajian Teologi Terhadap Percakapan Yudhiṣṭhira dan Bhisma) - Putu Dana Yasa (Sphatika: Jurnal Teologi, 2021)
The Mahābhārata War tells of the battle between the Pandavas and the Kauravas, which contains deep theological values. The teachings contained therein have become a guide in living life. In addition to divine values, in the great epic Mahābhārata also describes the teachings of a king's dharma as a guide for providing welfare to his people. This teaching was conveyed by Bhisma before he died on the battlefield of Kurukṣhtera to Yudhiṣṭira as the successor of the kuru dynasty. The dharma teachings of a king also contain divine values as the basis and guidance for a king in leading.